A movement intervention as a tool of the influence of physical fitness and health - Bunc, Václav (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The health benefits of PA are well established and include a lower risk of cardiovascular disease, hypertension, diabetes, and breast and colon cancer. Additionally, PA has positive effects on mental health, delays the onset of dementia, and can help the maintenance of a healthy body mass. Aim of Study. The aim of the study is to summarize the results of the application of appropriate PA based on walking on PF and health in non-trained Czech population differing in age. Material and Methods. The energy output on the level 950 to 2000 kcal (3971-8360 kJ) per week was respected by construction of individual moving programs for seniors, adults and children of both genders. The moving programs consisted of aerobic walking (min 80% of whole exercise) or cycling (min 10% of total exercise) at the level of 50 to 70% VO2 max. The duration of exercise session ranged from 20 to 50 min, and training was performed 3-5 times a week during 5 months. The functional variables were assessed on treadmill, body composition with help of bioimpedance analysis. The data were collected in children (142 boys and 124 girls; age 12.6 ± 2.3 years, BM = 36.9 ± 3.0 kg, height = 136.5 ± 2.6 cm, VO2peak = 43.2 ± 3.1 ml•kg–1•min–1) in both men (n = 154) and women (138) of middle age (45.2 ± 7.0,74.3 ± 3.9, 172.5 ± 2.6, 31.2 ± 3.9), and in seniors of both genders (men n = 71, women n = 112; 71.6 ± 3.6, 77.1 ± 4.1, 171.5 ± 2.9,26.1 ± 3.1). Results. Interventions with an energy content of 2000 kcal in children, 1500 kcal in adults and 950 kcal in seniors can reduce body mass (about 10%), improve VO2peak (~17%) and motor performance (~15%), reduce the systolic blood pressure(~7 mmHg) regardless of gender, starting values and age. It is also possible to significantly affect the amount of muscle mass (~8%). Conclusions. Reasonable PA is a prerequisite for quality lifestyle and active aging. For seniors, a higher level of PA and thus increased PF significantly affect the quality and progression of aging.
Keywords: physical activity; physical fitness; health; energy output